How Laypeople Understand the Tentativeness of Medical Research News in the Media: An Experimental Study on the Perception of Information About Deep Brain Stimulation. (April 2015) - Kimmerle, Joachim; Flemming, Danny; Feinkohl, Insa; Cress, Ulrike
Medical research findings are often tentative, and people should be able to perceive this. However, the psychological processes underlying this ability are largely unclear. In a laboratory experiment, we found that the following factors had an impact on perception of tentativeness of research findings reported in a newspaper article: (a) the framing of findings, (b) emphasis on the limited reliability of the findings in the article, (c) people's provisional opinion on the topic, and (d) their medicine-related epistemological beliefs. We make recommendations to science journalists to help promote the public understanding of health research and provide suggestions for future studies.